(3GdaQROb jfMJ ef UNQ hjgLh CeQ ef GdUHQ (B/s - (3GdMQ, YHO GdeLjOs ((3HjQhJ (B:s (3OGQ GdacQ GdYQHj,s, 1999)
(3jMJhj gPG GdcJGH HMKG TGedG ObjbG heQcRG Mhd eNJda GdbVGjG GdeJYdbI HgPG GdTGYQ(B.s
(3HHdjhLQGajI (B: (3U(B. 173-174.s
Keywords: (3GdaQROb, geGe Hf ZGdH Hf UYUYI,s -- (3Jhaj (B110 (3gLQjG(B.s; (3GdTYQ GdYQHjs -- (3GdYUQ GdCehj, (B661-750s